Estudio técnico de iluminación y su incidencia en las actividades educativas en el laboratorio de mecanizado de la carrera de ingeniería industrial, de la Universidad Técnica de Cotopaxi en el año 2017 - López Porras, Alex Bladimir (2017)
The machining laboratory of Industrial Engineering Career at Technical University of Cotopaxi showed deficiencies in its lighting systems, which causetroubles and complaints from students and teachers in their educational activities. The job with low light damages the view, also sudden changes of light can be dangerous, for that reason to get an appropriate level of visual comfort it must achieve a balance between the quantity, quality and stability of the light to control these effects it was conducted the technical study of lighting system and its impact in education, in addition it obtained students and teachersopinions which confirm the deficiencies, it can conclude the results of lightinglevels is 189.18 lux in the morning, 167.87lux in the afternoon and 135.81lux at night, the total average level is 164.29lux, show that do not reach with the European Standard of Lighting for educational institutions UNE-EN 12464-1 which is 500lux. The technological proposal is based on the best alternativechoice to change of lights of the current system as they are LED lamps, and the change of the lighting system that guarantees the development of illumination levels within the regulations to reduce the problems originates from the lighting in education, providing a safe and comfortable environment.